QSAR modeling and molecular docking studies on benzimidazole derivatives as anticancer agents - Nguyen, Hoang Phuc; Huynh, Thi Kim Chi; Thai, Khac Minh; Hoang, Thi Kim Dung (Vietnam Journal of Science and Technology, 2022)
Abstract. The triple-negative breast cancer cell line MDA-MB-231 has been known as one of the most tenacious cancer cancer cells and paid attention by many researchers. A two-dimension quantitative structure-activity relationship (2D-QSAR) model of 131 benzimidazole derivatives was developed to relate the chemical–biological interactions and predicted the half maximal inhibitory concentration (IC50) against MDA-MB-231 cell line. The 2D-QSAR model was obtained satisfactory internal and external validation parameters such as the square of correlation coefficient R2 = 0.904 and concordance correlation coefficient CCC = 0.867. The model was and applied on 35 synthesized benzimidazoles to predict IC50 values. The results showed that benzimidazoles with IC50 less than 50 µM displayed a quite similarity between predicted and experimental IC50 values (Ra2 = 0.924). The molecular docking study was investigated to clarify the binding mode of the most potential synthesized benzimidazoles (BLMM, and BL3H) into topoisomerase I-DNA complex. The docking results revealed that they intercalated and interacted to crucial amino acids in the binding site of complex by hydrogen bonds and hydrophobic interactions and compared to standard drug camptothecin.